MANAJAMEN KOMUNIKASI PENDIDIKAN DALAM PERSFEKTIF AL-QUR’AN - Muslimin Hutapea; Suheri Sahputra Rangkuti (HIKMAH: JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
The science development and information technology sophistication in the era of globalization that can be seen from television, internet and other media almost make the world has no boundary between regions and countries so that foreign cultures (from the west) which the majority deviates from the norms and rules of Islam are easily accepted by many countries including Indonesia. This condition causes young generation to experience a moral crisis that needs a serious attention from educators, especially parents in fortifying their children with a strong faith in order not to get carried away into the valley of error through the communication process that is managed effectively. To fortify a child with a strong faith, it is necessary to develop a concept of education derived from the Qur'an which is the first and main source of Islamic teachings. For that reason, a study entitled "The Management Concept of Communication Education in the Perspective of the Qur'an" was conducted. The study focuses on discussing the management concept of communication education in the perspective of the Qur'an. This study aims to determine the role of communication management in instilling education and to develop a concept ojnhgkmf educational communication management in the perspective of the Qur'an. It is a library research which is done by using rationalistic approach. The analysis method was content analysis. Then, the data were collected by using documentary method with thematic study model that comes from the Qur'an and other supporting resources such as books of interpretation and scientific books. The verses of the Qur'an which were studied contains interpersonal communications i.e. communication between two or more persons. The results indicate that the role of communication management is very urgent in instilling education to children. The Qur'an has explained on how to communicate effectively and efficiently with good communication so that it is easy for parents to introduce education such as aqidah, shariah, akhlak, and Tazkiyah. The concept of faith education contains the cultivation of faith. The concept of sharia education contains sacrificial education, prayer, and zakat. The concept of moral education contains the dutiful command to the parents, the mandate, and the morality. The concept of tazkiyah education contains patience and not spiteful and arrogant. Based on these findings, it can be understood that the concept of educational communication management in the perspective of the Qur'an has a number of rules that can be used as a guide for parents to educate their children to act and behave in accordance with the teachings of the Qur'an.